OPTIMALISASI KEBIJAKAN IZIN MENDIRIKAN BANGUNAN SEBAGAI UPAYA MEWUJUDKAN KOTA YANG TERTATA - Tati Sutriasih E.42008062 (FISIP Universitas Tanjungpura Pontianak, 2013)
This research aims to know the factors that influence the process of the implementation of thePolicy Building Permits in Sungai Ringin village in Sekadau Distric that has been done bySekadau Public Employment and The Mining Service especially Copyright and Natural ResourcesField in 2004 to 2011. This research uses a qualitative analysis of three stages of data analysis,there are data reduction, data presentation and conclusion. The subject in this research is SekadauGovernment that associated with Building Permit Policy implementation and around local societythat owns the building as a policy target. The result showed that policy implementation has notbeen maximum caused by several factors that said by Edward III. Recommendation for policy is todo a review of the factors that should be repaired associated with the next implementation ofBuilding Permit Policy, in order to suitable with the purpose.Keywords: Policy, Implementation, Building Permit.